Washing efficiency and fabric damage by beating and rubbing movements in comparison with a front-loading washer. Issue 6 (April 2017) - Yun, Changsang; Cho, Yoonkyung; Park, Chung Hee
The objective of this study was to evaluate washing performance by beating and rubbing movements that simulate traditional washing methods. By comparing washing performance between these washing methods and a front-loading washer, we examined the potential of the new washing technique and proposed an efficient washing system. In this study, the new rubbing movement, that mimics a washboard, shows low fabric damage with high washing efficiency. The rubbing movement provides high mechanical force, which allowed easy transfer between soil and the detergent solution on the fabric surface. Thus, efficient washing can be accomplished by rubbing movements which minimize fabric damage and achieve high washing efficiency. A beating movement that copies a laundry bat gave the lowest damage and washing performance, so may be used for delicate textiles. In addition, location changes through flexing enhanced washing efficiency and showed better performance than strong force in a fixed location.